Access Barriers to Dental Treatment and Prevention for Turkish Migrants in Germany – A Qualitative Survey - Spinler, Kristin; Kofahl, Christopher; Ungoreit, Erik; Heydecke, Guido; Dingoyan, Demet; Aarabi, Ghazal (Frontiers in Public Health, 2022)
Introduction: The worldwide migration movement is growing and thereby challenging the health care systems of immigration countries like Germany to make health care equally accessible for all people. Due to their low oral health status and low uptake rates of dental treatment and prevention, migrants were detected as a vulnerable group. Data regarding dental care access barriers of this group is limited. Therefore, the following study established a deeper understanding of unknown access barriers. Methods: Nine expert interviews and one focus group interview were conducted semi-structured via interview guideline in the period of August until October 2018. The experts were persons with strong vocational interactions and experiences with the sector oral health care and migration. The focus group participants had a Turkish migration background. Results: The expert and focus group interviews revealed a variety of barriers that exist towards dental treatment and prevention for migrants. Language, perceived significance of oral health, oral health knowledge, health socialization and patient-dentist interaction were detected to be the main barriers with underlying subthemes and interactions. Furthermore, a predominantly not precaution-oriented dental service utilization of migrants was underlined by the interviewees. Additionally, ways to reach a higher cultural sensitivity in oral health care were stated. Conclusion: With respect for research, there is a need for the integration of migrant-specific items when collecting health data from people. With respect for policy, there is a need for more structural and individual attention for promoting equal access to oral health care and prevention measures for people with a migrant background.